Public policies in open economies - Brunner, Karl; Meltzer, Allan H. (Amsterdam : New York : North-Holland Pub. Co. ; New York : sole distributors for the U.S.A. and Canada, Elsevier North-Holland, 1978)
This ninth volume of the series, offered as a supplement to the Journal of Monetary Economics, contains papers presented at the November 1977 conference.
Includes bibliographical references.
osc 15/01/2019
Loans
Keywords: Economic policy; Public policy